A retrospective study on surgical management of ovarian tumours in a teritary care semiurban hospital - Ranjitha, S. Divya; Karthikeyan, Kavitha; Nalini, Amrita Priscilla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The prevalance of ovarian tumors is around 1-3%. The accurate diagnosis and appropriate management of ovarian tumors is a real challenge to gynaecologists. The aim of the study was to analyse the risk factors, clinical presentation, surgical procedure and histopathological report in patients with surgically managed ovarian tumours. Methods: We conducted a retrospective study by collecting the data of patients operated in the department of Obstetrics and Gynecology at Chettinad Hospital and Research Institute, Kelambakkam. A total of 118 case records were studied. Results: 20.3% were nulliparous. 79.7% were multiparous. 10.2% were <20 years, 47.2% were 20-40 years, 39.2% were 40-60 years, 3.4% were >60 years. 72.9% were premenopausal. 27.1% were postmenopausal. 25.4% presented with acute abdominal pain, 11.9% with mass abdomen, 30.5% with chronic pain abdomen and 32.2% were incidentally diagnosed. 20.4% underwent ovarian cystectomy, 18.6% ovariotomy, 30.5% salpingoophorectomy and 30.5% total abdominal hystrectomy with bilateral salpingoophorectomy. Most common histopathology report was simple cyst in 44.%. 31.3% had serous cystadenoma, 9.3% had mucinous cystadenoma, 9.3% had teratoma, 2.5% had brenner tumour, 1.7% borderline tumours and 1.7% malignancy (Serous cystadenocarcinoma). Conclusions: Elective surgical management of ovarian tumours is better option for reducing emergency laparotomies for torsion and rupture and also for obtaining a conclusive histopathological diagnosis in suspicious cases. The choice between laparoscopy and laparotomy should made after making appropriate preoperative evaluation.